RANCANG BANGUN MULTIMEDIA PEMBELAJARAN KERAGAMAN BUDAYA MELALUI WARISAN BUDAYA INDONESIA DENGAN METODE HANNAFIN & PECK - Halda Salsabila; Teuku Mufizar; Cepi Rahmat Hidayat (Institut Teknologi dan Bisnis Swadharma, 2025)
Indonesia is rich in diverse cultures, including traditional weapons, dances, houses, clothing, and musical instruments. According to social studies teachers, students are well-acquainted with the cultural heritage of West Java; however, their knowledge of cultures from other provinces remains limited. To address this, a researcher developed an interactive learning media showcasing the cultural diversity of Indonesia's 34 provinces. Each province features five cultural heritages: traditional weapons, dances, houses, clothing, and musical instruments. The learning approach integrates audio, animations, images, and text to engage students more effectively, aiming to foster interest in traditional cultures and ensure their preservation. The application was designed using the Hannafin and Peck model, which comprises three main phases: needs assessment, design, development, and implementation. The study involved seventh-grade students from SMPN 13 Tasikmalaya. Student comprehension was assessed through pretests and posttests, resulting in an N-Gain score of 0.47, which falls into the